Immunohistochemical detection of TAS2R38 protein in human taste cells. - Maik Behrens (Public Library of Science (PLoS), 2012)
The sense of taste plays an important role in the evaluation of the nutrient composition of consumed food. Bitter taste in particular is believed to serve a warning function against the ingestion of poisonous substances. In the past years enormous progress was made in the characterization of bitter taste receptors, including their gene expression patterns, pharmacological features and presumed physiological roles in gustatory as well as in non-gustatory tissues. However, due to a lack in TAS2R-specifc antibodies the localization of receptor proteins within gustatory tissues has never been analyzed. In the present study we have screened a panel of commercially available antisera raised against human bitter taste receptors by immunocytochemical experiments. One of these antisera was found to be highly specific for the human bitter taste receptor TAS2R38. We further demonstrate that this antibody is able to detect heterologously expressed TAS2R38 protein on Western blots. The antiserum is, however, not able to interfere significantly with TAS2R38 function in cell based calcium imaging analyses. Most importantly, we were able to demonstrate the presence of TAS2R38 protein in human gustatory papillae. Using double immunofluorescence we show that TAS2R38-positive cells form a subpopulation of PLCbeta2 expressing cells. On a subcellular level the localization of this bitter taste receptor is neither restricted to the cell surface nor particularly enriched at the level of the microvilli protruding into the pore region of the taste buds, but rather evenly distributed over the entire cell body.